A case of sepsis‐induced cardiomyopathy successfully treated with venoarterial extracorporeal membrane oxygenation. Issue 1 (5th October 2022) - Sato, Keigo; Naito, Akihiro; Shiratori, Taichi; Yamamoto, Masahiro; Shimane, Kenichi; Mikami, Manabu; Senda, Mariko; Kume, Haruki; Suzuki, Motofumi
Abstract : Introduction: Sepsis with concomitant acute pyelonephritis, secondary to urolithiasis, is common. We report a case of sepsis‐induced cardiomyopathy with acute pyelonephritis, successfully managed with venoarterial extracorporeal membrane oxygenation. Case presentation: A 64‐year‐old woman presented with fever and disturbed consciousness. Abdominal computed tomography revealed right hydronephrosis with ipsilateral ureteral stone. Despite ureteral stent placement and antibiotic treatment, her hemodynamics worsened. She was diagnosed with sepsis‐induced cardiomyopathy and underwent venoarterial extracorporeal membrane oxygenation. Her hemodynamics improved rapidly; venoarterial extracorporeal membrane oxygenation was withdrawn on postoperative day‐3. She was discharged from our hospital after sufficient antibiotic treatment. Conclusion: Venoarterial extracorporeal membrane oxygenation may be initiated in patients with sepsis‐induced cardiomyopathy. Evaluation of left ventricular ejection fraction via echocardiography is important to determine the indication for venoarterial extracorporeal membrane oxygenation.